2020
DOI: 10.11157/fohpe.v21i2.397
|View full text |Cite
|
Sign up to set email alerts
|

Writing a manuscript for publication: An action research study with allied health practitioners

Abstract: Introduction: Writing a manuscript for publication is a challenge for those health practitioners whose primary role is to provide clinical services. The aim of this study was to increase the capacity of allied health practitioners who are employed in a clinical setting to submit manuscripts for publication in peer-reviewed journals.Methods: An action research study design was used to develop a “Writing for Publication” program for nine allied health practitioners who had not previously published a manuscript a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In their evaluation of a rurally based novice researcher training program, Duncanson et al 40 found that the peer support and peer learning elements of their training program were highly valued and contributed to participants' increased confidence and motivation to continue to engage in research activity. Other authors have reported on the benefits of peer learning and support featured in novice researcher training programs 42–44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their evaluation of a rurally based novice researcher training program, Duncanson et al 40 found that the peer support and peer learning elements of their training program were highly valued and contributed to participants' increased confidence and motivation to continue to engage in research activity. Other authors have reported on the benefits of peer learning and support featured in novice researcher training programs 42–44 …”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported on the benefits of peer learning and support featured in novice researcher training programs. [42][43][44] Nonetheless, organisational factors seemed to supersede the practical nature of the training with respect to influencing the outcomes and impacts of the training. This was evident in both the positive and negative sense.…”
Section: Discussionmentioning
confidence: 99%
“…In response to ongoing learner feedback and through peer teaching, we found we needed to develop our teaching approach for HPE research development. 29 This was particularly important when considering the context of these HPE research novices in a busy healthcare setting. 7 Through action research and peer collaboration, 5 we overcame challenges and modified our teaching beliefs and practices.…”
Section: Facilitators' Development As Teacher Educatorsmentioning
confidence: 99%
“…11 We will continue to collaboratively improve the course, working with the opportunities and limitations of healthcare workplaces, including competing priorities and distractions, which affect momentum. 29 Through continuing use of the cyclical action research methodology, 14 we will continue to evaluate redevelopments to the course and its impact, including the tracking of new HPE research projects initiated as a result of course participation.…”
Section: Facilitators' Development As Teacher Educatorsmentioning
confidence: 99%
“…Through collaboration and discussion with colleagues, educators can solve problems in their teaching and, by so doing, develop their teaching beliefs and practices (Beijaard & De Vries, 1997). Collaborative research practice, such as action research, can also facilitate professional development (Harvey et al, 2020).…”
mentioning
confidence: 99%